Practical Guidance for Radiological Risk Assessment in Educational and Research Laboratories - Kaissas, Ioannis; Mitrakos, Dimitris; Hourdakis, Costas (HNPS Advances in Nuclear Physics, 2022)
Using ionizing radiation, even in educational and research laboratories, is based on the triplet of principles of: justification, optimization and dose limits. These principles are applicable to the risk assessment that follows the identification of hazards in specific applications of ionizing radiation. In this work, a practical procedure for the development of risk assessments is provided for the majority of research and educational practices, which include the use of unsealed and sealed radioactive sources and apparatus with tubes producing ionizing radiation. In addition, an example of radiological hazard of fire is analyzed, in order to classify the severity of such risk on radioactive materials and sources. The severity of the hazard and consequently of the risk, the probability of the hazard to occur and the detectability of the occurrence are analyzed and combined to yield a risk classification, which induces the management of the measures taken for the emergency preparedness and response. The proposed methodology considers worst case scenarios of external exposure, inhalation and ingestion [1] and compares the doses with criteria like the annual dose limits or the reference band of 20 – 100 mSv [2], in order to initially classify the hazards and therefore the severity on the risk assessment procedure. The results indicate low or medium severity of the risks for most of the educational and research applications. Moreover, specifically the radiological hazard of fire for the public and the first responders is not high due to the relative low or moderate activities in use. Nevertheless application of the principle of optimization reduces even more the risks with the appropriate measures, like: controlled access, fire detectors and extinguishers, secure storage and keeping of records.